Optical Encryption of Arrays of Binary Digits in Spatially Incoherent Light - Krasnov, V. V.; Starikov, S. N.; Starikov, R. S.; Cheremkhin, P. A. (Russian physics journal, 2016)
Optical encryption of arrays of binary digits in spatially incoherent light is experimentally implemented. Successful optical encryption and numerical decryption of images of binary arrays using a developed setup is demonstrated. Faultless decryption of arrays with normalized average energies (NAEs) up to 0.3 inclusive has been implemented. It is demonstrated that a decrease in the NAE of arrays to be encrypted leads to a decrease in the encryption error rate.